Withdrawn: Phenomenological Study of Coexistence of Magnetism and Superconductivity in Heavy Fermions Systems by Multi-component Ginzburg-Landau Functional - Hinh, Nguyen Van; Lan, Nguyen Tri (Communications in Physics, 2016)
This article which was published online on 16 October 2016 has been withdrawn at the request of the editors and the authors. The Publisher apologizes for any inconvenience this may cause.